Choosing the Criteria for Clinical Evaluation of Composite Restorations: An Analysis of Impact on Reliabilty and Treatment Decision - Cleber Paradzinski Cavalheiro; Pablo Soares de Souza; Rachel de Oliveira Rocha; Fausto Medeiros Mendes; Mariana Minatel Braga; Daniela Prócida Raggio; Tathiane Larissa Lenzi (Association of Support to Oral Health Research (APESB), 2022)
Objective: To assess the reproducibility of two clinical criteria for the evaluation of restorations in primary teeth and the impact on treatment decision. Material and Methods: A cross-sectional study was performed selecting 71 resin-based composite restorations placed in primary molars of children who had sought dental treatment at a dental school. Two trained examiners evaluated independently the restorations using modified FDI and USPHS criteria. All restorations were assessed separately with each system in random order to avoid memory bias. Kappa statistics were used to determine inter-examiner reliability considering each parameter of both criteria and score final about treatment decision. McNemar test was used to compare the treatment decision with two criteria. The significance level was set at 5%. Results: Kappa values ranged from 0.28 to 0.93 with USPHS and 0.28 to 0.88 with FDI, considering each parameter separately. Inter- examiner agreement for treatment decision was excellent for both criteria (Kappa: 0.85-0.90). For clinical decision-making, no difference between criteria was found, irrespective of examiner. Conclusion: Low inter- examiner agreement for evaluation of each parameter of USPHS and FDI criteria does not reflect on reproducibility for treatment decision. Both criteria may be suitable for evaluation of composite restorations in primary teeth.